Spatial Analysis of The Influence of Residential Density on The Spread of Tuberculosis Cases in Pasar Rebo General Hospital Service Area - Efendi, Andi; Darwis, Teungku Ichramsyah (Cities and Urban Development Journal, 2023)
Background: Based on statistical data, in 2021 tuberculosis cases in the DKI Jakarta area reached 26,854, an increase of around 21% from 2020, 22,156 cases. Aims: This Study focuses on the lavel of administrative area whether a residential density shows significance in the spread of Pulmonary Turberculosis (TB) cases. Methods: The research carried out by a descriptive quantitative research in the Pasar Rebo General Hospital. Results: The distribution of patients in the Pasar Rebo General Hospital is not affected by the total population density found in a sub-district area. After the research was carried out in a smaller administrative scope, namely at the sub-district level, it was began to show a correlation between population density and the spread of pulmonary tuberculosis. Using a spatial approach, the research shows that there is a casual relationship between the cases of the spread of tuberculosis and the density of a residential area. Conclusion: Based on the data obtained and the spatial analysis, this study shows that the population density variable show the percentage level of the spread of a case of Pulmonary TB. But in this case it must be seen at a level of the smallest administrative area, namely at the sub-district level.